A microRNA-regulated transcriptional state defines intratumoral CD8+ T cells that respond to immunotherapy - William W. Tang; Ben Battistone; Kaylyn M. Bauer; Allison M. Weis; Cindy Barba; Muhammad Zaki Hidayatullah Fadlullah; Arevik Ghazaryan; Van B. Tran; Soh-Hyun Lee; Z. Busra Agir; Morgan C. Nelson; Emmanuel Stephen Victor; et al. (Cell Reports, 2025)
Summary: The rising incidence of advanced-stage colorectal cancer (CRC) and poor survival outcomes necessitate new and effective therapies. Immune checkpoint inhibitors (ICIs), specifically anti-PD-1 therapy, show promise, yet clinical determinants of a positive response are suboptimal. Here, we identify microRNA-155 (miR-155) as necessary for CD8+ T cell-infiltrated tumors through an unbiased in vivo CRISPR-Cas9 screen identifying functional tumor antigen-specific CD8+ T cell-expressed microRNAs. T cell miR-155 is required for anti-PD-1 responses and for a vital intratumor CD8+ T cell differentiation cascade by repressing Ship-1, inhibiting Tcf-1 and stemness, and subsequently enhancing Cxcr6 expression, anti-tumor immunity, and effector functions. Based on an underlying miR-155-dependent CD8+ T cell transcriptional profile, we identify a gene signature that predicts ICI responses across 12 diverse cancers. Together, our findings support a model whereby miR-155 serves as a central regulator of CD8+ T cell-dependent cancer immunity and ICI responses that may be leveraged for future therapeutics.